PERLINDUNGAN HAK ASASI MANUSIA TERHADAP HAK HIDUP ANAK DALAM KANDUNGAN DI LUAR PERKAWINAN YANG SAH - Lusiana Tijow (Universitas Negeri Gorontalo, 2010)
human rights is the most essential rights inherent in the human person at birth. son of the conceptual contect is the son of man human that sould be protected.conceptually this appreas problematic,because in theory all along,that the exiting child in the womb in the mother has the right to birth,while in fact many actions caried out abortions.in the criminal law any dilyberate abortion fetus(abortion)is prohibited because it contains the same meaning with murder. legal rules contained in the instruments of human rights,emhasized that the legal status of children who are stillin the womb,wheter inside or uar marriage,they both have an equal right to life ,liberty and safety as an individual. built relationships outside of mariage is not legally recognized in state practice and in paticular the lives of indegenous peopels in indonesia,the implication of causing his motherś tedency to end a childś life since she was in the womb.thought every child is entitled to can life,grow end developed in accordance with the dignity of humanity and get protection from violence and discrimation.goverment should look as other chilidren without discrimination keywords:protection, Chilidren, Life Rightds, in the womb, Legitimate outside marriage